Decoupled Nutrient Status: a framework to disentangle host from microbial responses to diets that vary in digestibility - Venable, Emily M.; Carmody, Rachel N. (Frontiers in Food Science and Technology, 2024)
Diet shapes the gut microbiome, which in turn influences host phenotype. Accordingly, there is much interest in leveraging diet to modulate gut microbial communities and host biology. However, recent approaches have not fully appreciated that hosts and gut microbes experience diet differently. Whether dietary nutrients reach the gut microbiota, which primarily resides in the colon in humans and other hindgut fermenters, depends on nutrient absorption in the small intestine. That gut microbes utilize the fraction of diet that escapes host-driven digestion creates a paradigm where host nutrient status is decoupled from, and often negatively correlated with, gut microbiome nutrient status. Here, we present a framework based on this concept of decoupled nutrient status (DNS), which can be used to understand distinct host and gut microbial phenotypes that are ultimately mediated by the small intestinal digestibility of the diet. We evaluate our framework against existing research employing diets of varying digestibility and demonstrate convergence of host phenotypes and gut microbial signatures across studies. Further, we highlight that gut microbial signatures predicted by DNS manifest most strongly in humans living industrialized lifestyles and in captive animals that habitually consume diets with high host-driven digestibility. We posit that the evolutionary decoupling of nutritional status between hosts and their gut microbiota has likely been especially pronounced in humans due to our intensified pursuit of calorie-rich, easy-to-digest diets. We conclude by proposing future research directions to better capture diet as it appears to gut microbes, a perspective likely to deliver new understanding of diet-microbiome interactions.